2021
DOI: 10.1111/dpr.12512
|View full text |Cite
|
Sign up to set email alerts
|

Community‐led reconstruction, social inclusion and participation in post‐earthquake Nepal

Abstract: Motivation: Disasters have terrible consequences for those affected, but do they also provide opportunities to challenge existing social divisions and inequalities and to promote democratic social change? Purpose: This article explores whether community-led reconstruction (CLR) can leverage progressive social change by increasing the participation and social inclusion of marginalized and excluded groups. The question it addresses is: to what extent and in what ways can CLR facilitate participation and social i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Moreover, a significant proportion of the population not only recovered well from the earthquake but also improved their overall quality of life, which are in line with the positive impacts of natural disaster in the longer term found in existing literature [56,57]. In the case of Nepal, the decentralized administrative structure with newly elected local to central governments under the new Constitution of Nepal in 2015 [58], the community-led owner-driven reconstruction, social inclusion and participation [59,60], and the donor community played crucial roles in these achievements [24,61].…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, a significant proportion of the population not only recovered well from the earthquake but also improved their overall quality of life, which are in line with the positive impacts of natural disaster in the longer term found in existing literature [56,57]. In the case of Nepal, the decentralized administrative structure with newly elected local to central governments under the new Constitution of Nepal in 2015 [58], the community-led owner-driven reconstruction, social inclusion and participation [59,60], and the donor community played crucial roles in these achievements [24,61].…”
Section: Discussionsupporting
confidence: 76%
“…On a more local level, one study after the Nepal earthquakes in 2015 found that the operational reliance of non-governmental organ isations on social capital to distribute support after a disaster contributed to inequities in access to resources. 152 Recovery processes 26 articles focused on elements of recovery from multiple disasters, including economic recovery, 153,154 government and political factors in the recovery stage, 53,66,[155][156][157][158][159][160] community capitals, 24 schools as central hubs for recovery, 161 disaster recovery committees, 162 inequalities in recovery, [163][164][165][166][167] and reconstruction experiences. 150,[168][169][170] This group also included articles on programmes undertaken in a recovery setting in low-income and middle-income countries, including a food security and relief programme, 171 a microcredit programme, 172 a recovery aid programme, 69 and a global water, sanitation, and hygiene (WASH) programme.…”
Section: Humanitarian and Non-governmental Organisation Responsesmentioning
confidence: 99%
“…92 • Develop inclusive recovery frameworks, committees, and support programmes that recognise the needs of diverse communities. 118,162,165,166,169 • Develop policy and interventions to support people in preventing, preparing for, and recovering from ongoing or recurring disasters. 164 Ensure that any recovery interventions do not overlook crucial social, cultural, political, and environmental factors that can influence the recovery process.…”
Section: Recoverymentioning
confidence: 99%
“…Previous studies have generally demonstrated that local inhabitants have specific capacities to facilitate long-term recovery [46], including political [47], social [48], leadership [49], and economic capacity [50]. As an illustration, Crawford and Morrison argue that the community-led reconstruction program after the 2015 Nepal earthquake repaired local social connections and promoted social inclusion through engaging with marginalized and under-represented groups [51]. Moreover, an evaluation of long-term livelihood recovery following the 2004 Indian Ocean tsunami in Aceh, Indonesia, demonstrated that local disaster survivors could utilize financial aid provided by external sponsors to restore their livelihoods to their pre-disaster levels [52].…”
Section: Rebuilding Lives and Livelihoodsmentioning
confidence: 99%
“…Likewise, disaster survivors in other nations have their unique expertise [4,52]. In other words, if these grassroots expertise capacities could be engaged in the official built environment planning and architectural design, the physical environment weaknesses would be reduced [51]. In doing so, the inhabitants would more easily adapt to their new communities, enhancing long-term recovery and advancing sustainable community development.…”
Section: Involving the Grassroots Place-making Expertise In The Official Plansmentioning
confidence: 99%